التفكير المرن وعلاقته بمستوى الطموح لدى طلبة الجامعة - رزيج، فيصل حمدي (الجامعة العراقية - مركز البحوث والدراسات الإسلامية, 2023)
يهدف البحث الحالي التعرف على التفكير المرن وعلاقته بمستوى الطموح لدى طلبة الجامعة. ومن خلال الإجابة على الأسئلة التالية: هل هناك فروق ذو دلالة إحصائية في مستوى التفكير المرن لدى طلبة كلية التربية للعلوم الإنسانية تبعاً لمتغير الجنس. هل هناك فروق ذو دلالة إحصائية في مستوى الطموح لدى طلبة كلية التربية للعلوم الإنسانية تبعاً لمتغير الجنس، هل هناك علاقة ارتباطية دالة إحصائياً بين التفكير المرن وبين مستوى الطموح لدى أفراد عينة البحث. واقتصر البحث على طلبة الجامعة للعام الدراسي (٢٠٢١- ٢٠٢٢). وتضمنت عينة البحث (400) طالباً وطالبة ولتحقق هدف البحث أعد الباحث مقياس التفكير المرن وتبنا مقياس مستوى الطموح. وعولجت البيانات إحصائياً باستخدام الحقيبة الإحصائية للعلوم الاجتماعية (Spss) وأظهرت النتائج ما يلي: لا توجد فروق ذو دلالة إحصائية في مستوى التفكير المرن لدى أفراد العينة تبعاً لمتغير الجنس. لا توجد فروق ذو دلالة إحصائية في مستوى الطموح لدى أفراد العينة تبعاً لمتغير الجنس. توجد علاقة ارتباطية دالة إحصائياً بين المتغيرين، التفكير المرن مستوى الطموح. وفي ضوء النتائج توصل الباحث إلى مجموعة من التوصيات والمقترحات. The current research aims to identify the level of flexible thinking and its relationship to curiosity among students of the College of Education for Human Sciences. And by answering the following questions: Are there statistically significant differences in the level of flexible thinking among university students according to the gender variable. Are there statistically significant differences in the level of curiosity among university students according to the gender variable, is there a statistically significant correlation between flexible thinking and the level of curiosity among the members of the research sample. The research was limited to university students for the academic year (2020-2021) The research sample included. (400) male and female students. To achieve the goal of the research, the researcher prepared a scale of flexible thinking and adopted) a scale of curiosity. The data were treated statistically using the statistical package for social sciences (SPSS) and the results showed the following: There are no statistically significant differences in the level of flexible thinking among the sample members according to the gender variable, no there is differences with indication Statistic in level Curiosity I have Individuals the sample according to for variable sex .There is a statistically significant correlation between the two variables, flexible thinking and curiosity. In light of the /.results, the researcher reached a set of recommendations and suggestions.
Keywords: علم النفس التربوي -- مهارات التفكير -- طلبة الجامعات